Seismic performance of an existing low-rise RC building considering the addition of a new storey - Güneş, Barış; Coşgun, Turgay; Sayın, Barış; Mangır, Atakan (Pontificia Universidad Católica de Chile, 2019)
In low-rise reinforced concrete (RC) buildings, structural design is generally performed considering the seismic effects as well as the vertical loads. However, there may be situations where the additional or unpredicted loads may be encountered during the service life of the buildings. The loads that are governed from a new storey addition during the service life is a good example for these additional loads. Since the reconstruction permits and building height limits specified by the authorities may vary in life-cycle of the structures, it is critical to decide the addition of a storey to an existing building considering the structural safety concerns. In this study, an existing low-rise RC building is modelled with an added storey (subsequently planned for construction), and numerical analyses are carried out considering the extra loads of this additional storey. The aim is to evaluate the seismic performance of the structure considering this unpredicted situation which was not taken into account in the original structural design. The suitability of the preliminary structural design project to the existing building was checked by the site investigations. The results of the numerical analysis were compared with the seismic code requirements, and the seismic performance level of the building is determined. The study is intended to be useful in determining the path to be followed for the determination of the seismic capacity if existing buildings are subjected to additional loads.
Keywords: RC Buildings; Storey Addition; Seismic Performance